TANGGUNG JAWAB HUKUM LABELISASI HALAL PELAKU UMKM PANGAN OLAHAN KEMASAN DI BANGKALAN - Galuh Widitya Qomaro (Universitas Islam Madura, 2023)
Halal food is a profitable business not only among Muslim-majority countries but also non-Muslim countries. Indonesia is a country with the largest Muslim population in the world, but Indonesia's position is only limited to the market and has not yet become an actor. The industry is the result of the development of a halal supply chain where the production of goods or services from upstream to downstream has halal standards and certification. In Indonesia, the number of halal certifications does not match the number of MSMEs in Indonesia, for example in Bangkalan district. No less than 166,768 units of micro, small and medium enterprises are located in Bangkalan by absorbing a workforce of approximately 210,003 people. The applicable procedure in granting this halal label permit is based on the halal certificate issued by the MUI. Many products of Micro, Small and Medium Enterprises include a halal label without having a halal certificate. This study aims to find out the factors that cause MSME producers of processed food in Bangkalan Regency to not have halal certification and identify the legal responsibility of packaged processed food MSME producers for halal labeling. The research was conducted by observing primary data in Bangkalan district and then interviewing the MSMEs. The implication of this research is that people can know and understand about law and halal labeling in developing their businesses.